DETERMINATION OF DIABETIC RETINOPATHY PREVALENCE AND MAJOR RISK FACTORS AMONG TYPE 2 DIABETIC PATIENTS IN NAWABSHAH DISTRICT. - Ayesha Khan1, Khan Mohammad Nangrejo2, Ali Muhammad Abbasi3, Arif Rabbani Dahri4, Ruqaya5, Waqar Ali Abbasi6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
INTRODUCTION: Diabetic Retinopathy (DR) is a chronic eye concern for developing blindness in the patients of T2DM in low and middle income countries. Globally, the prevalence of DR was reported to be around 75% among type 2 diabetic patients (T2DM) patients. However, in Pakistan the figure is approximately 28.7%. Clinically there are three stages of DR depends upon the severity of the disease known as non-proliferative (NPDR), proliferative DR (PDR) and diabetic macular edema (DME). OBJECTIVE: Thus, this study aims to investigate the prevalence of DR with respect to its categorized types and associated risk factors in T2DM patients localized in Nawab Shah District. METHODLOGY: It is a cross-sectional study comprised of in=381 subjects of DR ethical approval and informed consent was taken for volunteer participation. Detailed qestionare was filled out for the collection of sociodemographic data. Anthropometric and biochemical measures were estimated for all study participants. Data analysis is performed by SPSS v 22.0. RESULTS: In this study, the prevalence of DR was found to ibe around 44.4%. However, 36.5% prevalence rate is obtained for NPDR and 41.4% for iPDR ipatients. Though, smoking, hypertension, higher BMI and positive family history of diabetes found to be more abundant and showed an association with the pathogenesis of higher PDR diagnosis as compared to NPDR. Therefore, this study provides the first report on prevalence of DR in Nawab Shah District. Moreover, more studies are required to evaluate the association of this higher prevalence rate DR with the environmental and genetic aspects.